Possible causes for the decline in Adélie Penguin population numbers at anvers island, Western antarctic Peninsula - Christopher Gallacher (Annals of Marine Science - Peertechz Publications, 2019)
The impacts of climate change are evident even at the most remote places on the planet. This is especially apparent on the isolated Western Antarctic Peninsula (WAP). Anvers island, located on the WAP, has historically had low humidity and extremely low temperatures. Also, regular seasonality maintains equilibrium within the entire system, from which organisms evolved to match these climate patterns. However, recent studies on climate trends in the WAP show disturbances in the regularity of the seasons. Vaughan et al., [1], observed a warming rate during the winter months from 1991 to 2008 that was more intense than along any other studied location globally. Rising temperatures limit sea ice duration as melting occurs earlier. This warming event is altering habitat conditions, thus disrupting entire trophic systems from primary producers to top predators like Adélie penguins [2].